The role of macrophage subsets in and around the heart in modulating cardiac homeostasis and pathophysiology - Isidoro, Carmina Albertine; Deniset, Justin F. (Frontiers in Immunology, 2023)
Cardiac and pericardial macrophages contribute to both homeostatic and pathophysiological processes. Recent advances have identified a vast repertoire of these macrophage populations in and around the heart - broadly categorized into a CCR2+/CCR2- dichotomy. While these unique populations can be further distinguished by origin, localization, and other cell surface markers, further exploration into the role of cardiac and pericardial macrophage subpopulations in disease contributes an additional layer of complexity. As such, novel transgenic models and exogenous targeting techniques have been employed to evaluate these macrophages. In this review, we highlight known cardiac and pericardial macrophage populations, their functions, and the experimental tools used to bolster our knowledge of these cells in the cardiac context.